Gender Representations in Death and Burial Rituals: Perspectives from some cultural groups in Ghana - Eyifa, G.A.M. (West African Journal of Archaeology, 2012)
While the sex of a person is biologically determined at birth, gender is a social construct involving the sex-related roles of individuals in society (Renfrew and Bahn, 2008:230). When archaeologists examine human remains, it is essential to extract the maximum information while causing minimum damage to the remains themselves (ibid: 448). A considerable amount of information on the gender of human remains can be gained by understanding the cultural and archaeological contexts of the site under investigation. The cultural practice involved in positioning of the body in a grave, the accompanying grave goods and examination of the shape of the pelvis and other bones left intact, gives clues to the gender interpretation of the human remain and the archaeological data. In addition, ethnographic studies, oral traditions and historical records provide insights that guide interpretations. This article looks at how the concept of gender is constructed among the living and also how various cultures construct burials to reflect gender. The implication of such gender constructs on archaeological interpretation of burials is also a focus of this paper.